2013
DOI: 10.1136/bcr-2012-007272
|View full text |Cite
|
Sign up to set email alerts
|

Kearns-Sayre syndrome presenting as isolated growth failure

Abstract: SUMMARY Failure to thrive arises from a heterogeneous group of paediatric disorders including defects in energy metabolism such as mitochondrial diseases. Illustrating this, we describe a girl with poor growth who eluded diagnosis until she developed characteristics of Kearns-Sayre syndrome. Her history emphasises that defects of energy metabolism can present as isolated growth failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The patient was diagnosed with KSS based on the typical pathological results and clinical manifestations. Previous reports have described endocrine disorders, including insulin‐dependent diabetes mellitus, hypothyroidism, hypoparathyroidism and nonautoimmune Addison's disease, accompanying KSS (Holloman et al., ; Obara‐Moszynska et al., ; Quade et al., ), but there are no reports of their coexistence in a male with KSS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The patient was diagnosed with KSS based on the typical pathological results and clinical manifestations. Previous reports have described endocrine disorders, including insulin‐dependent diabetes mellitus, hypothyroidism, hypoparathyroidism and nonautoimmune Addison's disease, accompanying KSS (Holloman et al., ; Obara‐Moszynska et al., ; Quade et al., ), but there are no reports of their coexistence in a male with KSS.…”
Section: Discussionmentioning
confidence: 99%
“…KSS is caused by mtDNA rearrangements, and more than 150 different mtDNA deletions have been found to cause this syndrome (Holloman et al., ; Obara‐Moszynska et al., ). However, no mtDNA mutation was detected in blood cells collected from this patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adenosine triphosphate (ATP) provides energy to drive different processes in the cells. The ATP levels in patients with KSS are reported to be disturbed, and alterations in intracellular ATP production is classically the main energy defect detected in these patients [ 24 ]. Interestingly, in the current study, we found no change in ATP levels in PBMNC derived iPSC of both KSS patients compared to iPSC from PBMNC of healthy individuals ( Figure 4 A).…”
Section: Resultsmentioning
confidence: 99%